Communique 11th International Conference of Islamic Economics and Finance Report and Post Conference Agenda 11th ICIEF Rethinking Islamic Economics and Finance: Paving the Way Forward for Inclusive and Sustainable Development - Haneef, Mohamed Aslam (2017)
The 11th International Conference on Islamic Economics and Finance (11th ICIEF) was successfully held in Kuala Lumpur from 11th to 13th October 2016 under the auspices of the International Islamic University Malaysia (IIUM), co-organised with the Islamic Research and Training Institute (IRTI) of the Islamic Development Bank Group, the International Association for Islamic Economics (IAIE) as well as the Ministry of Finance, Malaysia as strategic partner.